GLYCEMIC CONTROL IN CONTINGENT SITUATIONS: A LOOK INTO THE HbA1c OF PERSONS WITH DIABETES MELLITUS DURING THE COVID-19 PANDEMIC IN METRO MANILA - Alcaraz-Fajardo, Maylynn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Coronavirus Disease-2019 (COVID-19) was declared by the World Health Organization as a pandemic last March 11, 2020. Different governments enforced different measures like imposition of lockdowns to control the spread of the disease. However, lockdowns have adverse effects. This study aimed to determine the effect of quarantine restrictions caused by the COVID-19 pandemic on the glycemic control of adult patients with type 2 diabetes mellitus at the East Avenue Medical Center. It also aimed to identify socioeconomic and lifestyle changes that affected glycemic control during the lockdown. METHODOLOGY This study compared glycemic control of people with type 2 diabetes mellitus pre- and post-imposition of community quarantine during the COVID-19 pandemic. This study analyzed factor/s that affected glycemic control in such a contingent situation. It is a cross-sectional analytic study that examined HbA1c as a measure of glycemic control. Specifically, it compared HbA1c taken from patients with type 2 diabetes mellitus before the Enhanced Community Quarantine in Metro Manila and compared it with HbA1c taken post-ECQ/MECQ. It also identified other factor/s that affected glycemic control present in a lockdown. RESULTS A total of 120 patients with type 2 diabetes mellitus participated in the study. The median HbA1c prior to ECQwas 8.0 while the median HbA1c post-ECQ/MECQ was 8.23. Median fasting blood sugar was 144.88 mg/dl prior to quarantine which increased to 158.05 mg/dl after ECQ/ MECQ. CONCLUSION Increases in the median HbA1c and FBS were noted among the patients; however, only the increase in FBS was statistically significant. There was also a statistically significant lesser risk of having poor glycemic control when patients adhered to medications. Efforts toward addressing different factors in contingent times like these should be made. This study can serve as an example for future contingent situations (e.g., natural disasters or war).